DINAMIKA MEDIA FOTO RELATION HUMAS POLRES BAUBAU DAN MEDIA LOKAL - Aldin Aldin; Muh. Hidayatullah; Hastuti Hastuti (Institut Seni Indonesia Yogyakarta, 2025)
DYNAMICS OF MEDIA RELATIONS BETWEEN BAUBAU POLICE PUBLIC RELATIONS AND LOCAL MEDIA. This study analyzed a survey entitled